Indium and antimony distribution in a sphalerite from the “burgstaetter gangzug” of the upper harz mountains pb-zn mineralization - Schirmer, Thomas; Ließmann, Wilfried; Macauley, Chandra; Felfer, Peter (Minerals, 2020)
The sphalerite from the Burgstaetter Gangzug, a vein system of the Upper Harz Mountain nearby the town of Clausthal-Zellerfeld, exhibits a very interesting and partly complementary incorporation pattern of Cu, In and Sb, which has not yet been reported for natural sphalerite. A sphalerite specimen was characterized with electron probe micro-analysis (EPMA) and atom probe tomography (APT). Based on the EPMA results and a multilinear regression, a relation expressed as Cu = 0.98In + 1.81Sb + 0.03 can be calculated to describe the correlation between the elements. This indicates, that the incorporation mechanisms of In and Sb in the structure differ substantially. Indium is incorporated with the ratio Cu:In = 1:1 like in roquesite (CuInS2), supporting the coupled substitution mechanism 2Zn2+ → Cu+ + In3+. In contrast, Sb is incorporated with a ratio of Cu:Sb = 1.81:1. APT, which has a much higher spatial resolution indicates a ratio of Cu:Sb = 2.28:1 in the entire captured volume, which is similar to the ratio calculated by EPMA, yet with inhomogeneities at the nanometer-scale. Analysis of the solute distribution shows two distinct sizes of clusters that are rich in Cu, Sb and Ag.
CRIS-Team Scopus Importer:2020-09-18
Keywords: Antimony; APT; Element distribution; EPMA; Indium; Pb-Zn-mineralization; Sphalerite; Upper Harz Mountains